Multi-domain Task-oriented Dialog Challenge II - Li, Jinchao; Zhu, Qi; Peng, Baolin; Liden, Lars; Liang, Runze; Takanobu, Ryuichi; Shayandeh, Shahin; Shukla, Swadheen; Zhang, Zheng; Minlie Huang; Gao, Jianfeng (The Ninth Dialog System Technology Challenge, 2020)
There has been an increasing interest in building a dialog system crossing multiple domains to accomplish a complex goal. With the success of Multi-Domain Task Completion Dialog Challenge in DSTC-8 Track 1, we continue with the effort of building dialog systems under the multi-domain setting in this proposal. Compared with the previous challenge, in this track, we extend the tasks by incorporating new datasets, creating new sub-tasks, and providing a new development platform. We specifically focus on two aspects of dialog systems: language portability and end-to-end system complexity.